2018
DOI: 10.1002/sres.2560
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Information Acquisition and Processing in Decision‐Making by Individual within Insects Colonies

Abstract: Insects usually present simple behaviours, but their information processing abilities result in complex collective behaviours, allowing them to perform task allocation and solve difficult problems. Biologists have invested efforts to better understand the mechanisms that govern the behaviour of social insects at the individual level and that allow the emergence of complex behaviours at the colony level. Based on biological researches, we identify the main mechanisms used to acquire different types of informati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 68 publications
1
0
0
Order By: Relevance
“…Own pathogen load seems to be assessed by the ants indirectly, requiring social feedback by others in the form of received grooming – which must be targeted preferentially towards the infectious ants for this mechanism to work. Finally, we found that the ants become more reactive to socially-acquired information when they also individually acquire information on their own disturbance, reiterating the relevance of combined internal and external information integration in social insects 55 , 56 .…”
Section: Discussionsupporting
confidence: 67%
“…Own pathogen load seems to be assessed by the ants indirectly, requiring social feedback by others in the form of received grooming – which must be targeted preferentially towards the infectious ants for this mechanism to work. Finally, we found that the ants become more reactive to socially-acquired information when they also individually acquire information on their own disturbance, reiterating the relevance of combined internal and external information integration in social insects 55 , 56 .…”
Section: Discussionsupporting
confidence: 67%